Features of the Emergence and Re-Emergence of Infectious Diseases, Geopolitics and Gain-of-Function Research - Chrysanthus, Chukwuma Sr (International Journal of Coronaviruses, 2022)
This paper attempts to present the dissemination and transmission dynamics of emerging and reemerging infectious diseases and the underlying features of gain-of-function research and geopolitics in the ambient within and across borders. Research and publication are relevant from perspectives in the management of local and global health because disease is perspicuously a geopolitical issue ostensibly linked to gain-of-function research where health diplomacy undergirds present and future global functionalities regarding the emergence and reemergence of infectious diseases. These have generated vehement reactions with propensity for extreme geopolitics and gain-of-function natural and anthropogenic activities. Geopolitical parameters and gain-of-function issues impact on the social determinants of health and vice versa. The convening and convergence of countries for unprecented epidemic or pandemic treaty settings or other formulations to confront emerging and reemerging infectious diseases will afford considerable opportunities concerning challenges in action, preparedness and response. Provisions are pertinent for legal instruments, effective and efficient systems to curb future threats and outbreaks of infectious diseases.
Keywords: Vaccines; treatment; AIDS; HIV; SARS-CoV-2; vulnerable populations